City marketing: A look at its research trajectory through bibliometric analysis - Cotrina-Coral, Greysi Samantha (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. A bibliometric study was conducted to identify research patterns around the city marketing topic. Design/Methodology/Approach. We extracted documents from Scopus from 2000 to 2023. We then analyzed scientific production to identify productivity patterns at the institutional, journal, and author levels. Furthermore, the study employed network analysis to map the co-occurrence of terms and the co-citation of documents and journals. This was achieved using analytical tools such as VOSviewer, which enabled the visualization of connections and the identification of the most influential topics and literature. Results/Discussion. Regarding geographical distribution, most of the most productive institutions are located in Europe, which suggests that this continent is at the vanguard of research in this field. The most productive journals are Information Communication Technologies and City Development and Cities. The researcher with the most publications is Escourido-Calvo, M., with five articles. Subsequently, several authors have published four articles, including Barajas, A., Braun, E., Karachalis, N., and Kavaratzis, M. The word clustering revealed three main themes: urban planning and development, city branding, and economic aspects of cities. The co-citation of journals revealed that the most prominent journals are on urbanism, geography, market research, and sustainability. Four clusters were identified with the co-citation of documents: Cluster 1: Urban Planning and City Image Management, Cluster 2: Urban Competitiveness and Economic Development, Cluster 3: Urban Image and Public Perception, and Cluster 4: Urban Culture and Regeneration. Conclusions. This analysis indicates that European institutions predominantly research city marketing, a field well-represented in various academic journals on technology, sustainability, and innovation. The network analysis showed that cities utilize branding and marketing strategies to position themselves in a global market. From urban planning to image management, competitiveness, and culture, cities engage in a process of self-promotion, not only to attract tourists but also to attract investment and talent. The literature indicates that developing a robust brand identity, which incorporates economic, cultural, and administrative elements, is crucial.